URGENSI MEMBANGUN SISTEM EKONOMI ISLAM DI INDONESIA PERSPEKTIF AL-QUR’AN - Doli Witro (Ekonomi Islam, 2020)
In life, Islam teaches its adherents to strive for happiness in the world and the hereafter. Likewise with happiness when living life in the world, namely physical and spiritual prosperity. In preventing economic chaos, conflicting interests in economic problems must be minimized, supported by all legal regulations in a society. So it is very necessary a system that regulates the rights and obligations of the community in the state, especially in the economic sector based on the Qur‘an and Sunnah. The economic system implemented in Indonesia at the moment is arguably not good. When viewed from all existing systems, the capitalist system has mastered various lines to make society range to poverty. To measure economic growth the welfare indicators of a community are used. This success was marked by an increase in per capita income. This paper will discuss how the Islamic economy perspective of the Qur‘an. And how is the urgency to build the economic community in Islam? This is important to discuss, to remind the public about the existence of capitalists in the economic system and to provide mutual understanding to help fellow members of society, between the rich and the poor so that from these aids help social inequalities and social stratification can be minimized and then narrowed even can overcome. Keywords: Islamic Economics, Indonesia, Al-Qur‘an.